The Military Lens : Doctrinal Difference and Deterrence Failure in Sino-American Relations - Twomey, Christopher P. (Book collections on Project MUSE., 2010)
In The Military Lens, Christopher P. Twomey shows how differing military doctrines have led to misperceptions between the United States and China over foreign policy-and the potential dangers these might pose in future relations. Because of their different strategic situations, histories, and military cultures, nations may have radically disparate definitions of effective military doctrine, strategy, and capabilities. Twomey argues that when such doctrines-or "theories of victory"--Differ across states, misperceptions about a rival's capabilities and intentions and false optimism about one's own are more likely to occur. In turn, these can impede international diplomacy and statecraft by making it more difficult to communicate and agree on assessments of the balance of power. When states engage in strategic coercion-either to deter or to compel action-such problems can lead to escalation and war. Twomey assesses a wide array of sources in both the United States and China on military doctrine, strategic culture, misperception, and deterrence theory to build case studies of attempts at strategic coercion during Sino-American conflicts in Korea and the Taiwan Strait in the early years of the Cold War, as well as an examination of similar issues in the Arab-Israeli conflict. After demonstrating how these factors have contributed to past conflicts, Twomey amply documents the persistence of hazardous miscommunication in contemporary Sino-American relations. His unique analytic perspective on military capability suggests that policymakers need to carefully consider the military doctrine of the nations they are trying to influence.